A regularized hidden Markov model for analyzing the 'hot shoe' in football. (December 2022) - Ötting, Marius; Andreas, Groll
We propose a penalized likelihood approach in hidden Markov models (HMMs) to perform automated variable selection. To account for a potential large number of covariates, which also may be substantially correlated, we consider the elastic net penalty containing LASSO and ridge as special cases. By quadratically approximating the non-differentiable penalty, we ensure that the likelihood can be maximized numerically. The feasibility of our approach is assessed in simulation experiments. As a case study, we examine the 'hot hand' effect, whose existence is highly debated in different fields, such as psychology and economics. In the present work, we investigate a potential 'hot shoe' effect for the performance of penalty takers in (association) football, where the (latent) states of the HMM serve for the underlying form of a player.